Network structure reveals clusters of associations between childhood adversities and development outcomes - Sheridan, Margaret A.; Shi, Feng; Miller, Adam B.; Salhi, Carmel; McLaughlin, Katie A. (Developmental science, 2020)
Exposure to childhood adversity is common and associated with a host of negative developmental outcomes. The most common approach used to examine the consequences of adversity exposure is a cumulative risk model. Recently, we have proposed a novel approach, the dimensional model of adversity and psychopathology (DMAP), where different dimensions of adversity are hypothesized to impact health and well‐being through different pathways. We expect deprivation to primarily disrupt cognitive processing, whereas we expect threat to primarily alter emotional reactivity and automatic regulation. Recent hypothesis‐driven approaches provide support for these differential associations of deprivation and threat on developmental outcomes. However, it is not clear whether these patterns would emerge using data‐driven approaches. Here we use a network analytic approach to identify clusters of related adversity exposures and outcomes in an initial study (Study 1: N = 277 adolescents aged 16–17 years; 55.1% female) and a replication (Study 2: N = 262 children aged 8–16 years; 45.4% female). We statistically compare our observed clusters with our hypothesized DMAP model and a clustering we hypothesize would be the result of a cumulative stress model. In both samples we observed a network structure consistent with the DMAP model and statistically different than the hypothesized cumulative stress model. Future work seeking to identify in the pathways through which adversity impacts development should consider multiple dimensions of adversity. Network analysis of assocaitions among Sexual abuse (SA), Physical abuse (PA), Physical neglect (PN), Direct community violence (CV), Family violence (FV), Emotional stroop adaptation (ES‐adapt), Overall performance on emotional stroop (ES‐overall), Performance matrix reasoning (WASI‐M), Performance vocabulary (WASI‐V), Arrows switching task (switching), PASAT time to quit (PASAT), Parent 1 education (ED1), and Parent 2 education (ED2) reveal a two cluster solution with one cluster characterized by parent education and cognitive function while the other is characterized by exposure to maltreatment and emotional reactivity.